Polymer/zinc hybrid-flow battery using block copolymer micelles featuring a TEMPO corona as catholyte. Issue 9 (4th February 2016) - Winsberg, Jan; Muench, Simon; Hagemann, Tino; Morgenstern, Sabine; Janoschka, Tobias; Billing, Mark; Schacher, Felix H.; Hauffman, Guillaume; Gohy, Jean-François; Hoeppener, Stephanie; Hager, Martin D.; Schubert, Ulrich S.
Abstract : A poly(TEMPO methacrylate)-poly(styrene) block copolymer was utilised as catholyte in polymer/zinc hybrid flow batteries. Abstract : A well-defined block copolymer was applied in a semi-organic polymer hybrid-flow battery (pHFB). A 2, 2, 6, 6-tetramethylpiperidinyl- N -oxyl (TEMPO) containing polymer was utilised as cathode active material. Micellar structures of the active material were achieved by utilising a diblock copolymer composed of a polar poly(TEMPO methacrylate) (PTMA) and an unpolar poly(styrene) (PS) block, which enables the formation of core-corona micelles in organic carbonates. The synthesised PTMA- b -PS was electrochemically investigated and subsequently utilised as catholyte in polymer/Zn pHFBs. The constructed flow batteries feature an excellent cycling stability of 1000 consecutive charge/discharge cycles with 95% retention of initial discharge capacity and a stable voltage range of 2 V. Further, the charging process leads to slight changes in the micellar structure combined with an increased solubility.